Postoperative cerebral infarction after revascularization in patients with moyamoya disease: Incidence and risk factors - Wang, Jiaxiong; Jiang, Hanqiang; Tang, Jinwei; Lin, Chi; Ni, Wei; Gu, Yuxiang (Frontiers in Neurology, 2022)
Objectives Cerebral infarction is the major complication of revascularization surgery in patients with moyamoya disease (MMD), and we analyzed the possible causes of cerebral infarction after revascularization surgery for MMD. Methods MMD patients who were admitted and underwent surgical revascularization at Shanghai Huashan Hospital from January 2019 to December 2021 were retrospectively analyzed. Results A total of 815 patients and 890 revascularization surgeries (677 first revascularization surgeries and 213 second revascularization surgeries) were included in this study; 453 (50.9%) were performed on the left side and 437 (49.1%) on the right side, with 779 (87.5%) combined procedures and 111 (12.5%) indirect bypasses included. The mean patient age at the time of these procedures was 44.6 ± 11.7 years (range 6–72 years). Postoperative cerebral infarctions were observed in 46 (5.17%) surgeries, among which 31 occurred after left hemisphere revascularization surgeries, with an incidence of 6.84%, and 15 occurred after right hemisphere revascularization surgeries, with an incidence of 3.43%. Of these, 30 (65.2%) occurred in the operated hemispheres, 2 (4.3%) in the contralateral hemisphere and 13 (28.3%) in the bilateral hemisphere. There were 11 cases of massive infarction (23.9%). The incidence of postoperative infarction in patients undergoing the first revascularization was 6% (41/677) and 2.3% (5/213) in the second revascularization surgeries. Initial presentation as infarction (P <0.001), initial presentation as hemorrhage (P<0.001), hypertension (P = 0.018), diabetes (P = 0.006), 1st or 2nd surgery and surgical side (P = 0.007) were found to be related to postoperative cerebral infarction. Initial presentation as infarction (OR = 2.934, 95% CI 1.453-5.928, P = 0.003), initial presentation as hemorrhage (OR= 0.149, 95% CI 0.035-0.641, P =0.011), and 1st or 2nd surgery and surgical side (OR = 1.66, 95% CI 1.106–2.491, P =0.014) were independently associated with cerebral infarction after revascularization surgeries. Conclusions In patients with MMD undergoing surgical revascularization, initial presentation as infarction and first revascularization surgery performed on the left hemisphere are independent risk factors for postoperative cerebral infarction, whereas initial presentation as hemorrhage is a protective factor.